An investigation into loss and gain in english – vietnamese translational versions of subtitles of oscar winning movies from 2010 to 2014 - Thiều, Thiều Hoàng Mỹ (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis has been done in an effort to investigate the Loss and Gain in English Vietnamese translational versions of Oscar winning movies’ subtitles in terms of syntax and lexis. The methods selected to analyze the syntactic and lexical features are a combination of research methods such as descriptive method, qualitative and quantitative method. The findings of thesis present that the loss and gain phenomena in translation are unavoidable due to the differences and varieties between the two languages. These translational versions of works of art are more or less influenced by different languages and cultures. This study is also expected to be helpful for people whose works are in the fields of translation practice, cross cultural communication and foreign language teaching and learning